al-Wujūd al-Burtughālī fī ʿUmān fī ‘l-Maṣādir al-Maḥalliyya al-ʿUmāniyya - Ghannām, Sulaymān Muḥammad al- (Studies in the history of Arabia. Proceedings of the first international symposium on studies in the history of Arabia, 23rd – 28th April 1977, sponsored by the Department of History, Faculty of Arts, University of Riyadh, Saudi-Arabia, 1979)
With regard to the Portuguese presence in Oman, the following sources are mentioned: Ibn Qayṣar: K. Sīrat al-Imām al-ʿĀdil Nāṣir b. Murshid (118-119); Anonymous: Kashf al-Ghumma (119); Ibn Ruzayq: al-Fatḥ al-Mubīn (119); Sālimī: Tuḥfat al-Aʿyān (119-120); Anonymous: [no title]; Anonymous: [no title]. Pp. 121-124: text from Ibn Qayṣar’s work on the period of Imam Nāṣir b. Murshid; p. 124: short text from Kashf al-Ghumma.
Keywords: Relations -- Oman -- Portugal